Optymalizacja Kształtu Pręta Smukłego Umieszczonego w Strumieniu Płynu - Drąg, B.; Gajewski, A. (Engineering Transactions, 1974)
The rod is replaced by a model with a two degrees of freedom (Ziegler model) in order to solve the problem of optimization of the form of a rod placed in parallel fluid flow and subjected to simultaneous action of lateral and axial pressures (during the motion). The lateral pressure is assumed to be given by a very simple flow rule (piston rule), and the axial force changes its orientation within the entire range of the tracking coefficient. Using both the static and kinematic stability criteria, the stability defined volume of the Ziegler model is minimized at a given critical velocity of the fluid. The solution derived is accurate for the model, and represents only an approximation for the actual rod; however, it may serve as a general information on the character of optimal rod forms in fluid flows.